Indigenous intellectuals embrace anthropology. Will it remain the same? (Anuário Antropológico, 2023)
The growing number of indigenous students enrolled in graduate programs in anthropology is spawning a grouping of indigenous intellectual who, bringing their own knowledge to academia, have great potential to challenge the discipline’s convictions and open new vistas. One hopes the arrival of indigenous scholars in anthropology will expose its illusions, fallacies, blind spots, and contradictions and retrieve it from its present lethargy. The diversity of indigenous knowledge ought to provoke a shift toward an “ecumenical anthropology” willing to embrace new knowledge forms and contents, and benefit from them on equal terms rather than continuing to use them as mere raw material for often idle theories.